An approach to reduce labor pain and increase vaginal birth rate - Gangwar, Archana; Gupta, Sudhir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Labor pain is considered one of the most intense pains experienced by women. Effective pain management is crucial in enhancing maternal satisfaction and ensuring a positive childbirth experience. The peri-pudendal block (PPB) is a promising alternative to conventional pain management strategies during the second stage of labor. This study evaluated the efficacy of the peri-pudendal block in reducing labor pain, episiotomy rates, and improving maternal and neonatal outcomes. Methods: A prospective randomized controlled trial was conducted at BRD Medical College, Gorakhpur, involving 206 women with term pregnancies. Participants were divided into two groups: those receiving PPB (n=107) and those receiving standard care (n=99). Visual analogue scale (VAS) scores, duration of the second stage of labor, episiotomy rates, perineal injuries, and neonatal outcomes (APGAR scores) were assessed. Results: PPB significantly reduced VAS scores in both primiparous and multiparous women (4.61±0.12 and 4.36±0.78, respectively). The second stage of labor was shorter in the PPB group for both primiparous (51.52±5.80 minutes) and multiparous women (24.49±4.23 minutes). Episiotomy rates were significantly lower in the PPB group (63% for primiparous and 26.4% for multiparous women). No significant differences in neonatal APGAR scores or maternal cardiovascular parameters were observed. Conclusions: The peri-pudendal block is a safe and effective analgesic option during labor, improving maternal comfort and reducing surgical interventions without compromising neonatal outcomes.